Analysis of the Relationship Between Self-Efficacy, Adherence With Diet Therapy and Fluid Control in Patients Receiving Hemodialysis Treatment: A Structural Equation Analysis - Turan, Guelcan Bahcecioglu; Karabulut, Ceren; Ozer, Zulfunaz (Wiley, 2026)
PurposeHemodialysis treatment presents physical, emotional, and social challenges for patients, impacting their overall well-being and daily life. Successful management requires adherence to fluid restrictions, dietary guidelines, and regular medication intake. This study explored the associations between self-efficacy, dietary adherence, and fluid control in patients undergoing hemodialysis.MethodsThis cross-sectional, descriptive study was conducted from 15 April 2024 to 15 June 2024, involving 197 patients receiving hemodialysis at a public hospital and a private dialysis center in Erzurum, eastern Turkey. Data were collected using a Personal Information Form, the General Self-Efficacy Scale, the Fluid Control in Hemodialysis Patients Scale, and the Attitude Scale for Dietary Therapy of Hemodialysis Patients. Descriptive statistics and structural equation modeling were used for analysis. A Bayesian estimator assessed direct and indirect relationships between variables. The model's reliability and validity were assessed using various statistical tests.ResultsParticipants had an average age of 53.3 years and an average duration on dialysis of 6.7 years. Of the participants, 91.4% regularly monitored their weight, and 65% regularly monitored edema. The average scores were 28.35 (5.92, SD) on the General Self-Efficacy Scale, 45.8 (8.12) on the Attitude Scale for Dietary Therapy, and 49.0 (9.05) on the Fluid Control Scale. Self-efficacy had a significant positive indirect association with fluid control through dietary adherence (beta = 0.126, 95% confidence interval [0.008, 0.277]). The total association between self-efficacy and fluid control was also significant (beta = 0.624, 95% confidence interval [0.483, 0.755]), with dietary adherence partially mediating this relationship. Self-efficacy accounted for 31% of the variance in dietary adherence, and the overall model explained 41% of the variance in fluid control.ConclusionHigher self-efficacy was associated with better dietary adherence and improved fluid control. Dietary adherence partially mediated the association between self-efficacy and fluid control. Healthcare providers may consider strategies to enhance self-efficacy in hemodialysis patients to support dietary adherence and fluid control, potentially improving treatment outcomes, and quality of life.
Keywords: adherence; diet therapy; fluid control; hemodialysis; nurse; self-efficacy